The Role of Metabolic Dysfunction in T-Cell Exhaustion During Chronic Viral Infection - Zheng, Kehong; Zheng, Xiaojun; Yang, Wei (Frontiers in Immunology, 2022)
T cells are important components of adaptive immunity that protect the host against invading pathogens during infection. Upon recognizing the activation signals, naïve and/or memory T cells will initiate clonal expansion, trigger differentiation into effector populations and traffic to the inflamed sites to eliminate pathogens. However, in chronic viral infections, such as those caused by human immunodeficiency virus (HIV), hepatitis B and C (HBV and HCV), T cells exhibit impaired function and become difficult to clear pathogens in a state known as T-cell exhaustion. The activation and function persistence of T cells demand for dynamic changes in cellular metabolism to meet their bioenergetic and biosynthetic demands, especially the augmentation of aerobic glycolysis, which not only provide efficient energy generation, but also fuel multiple biochemical intermediates that are essential for nucleotide, amino acid, fatty acid synthesis and mitochondria function. Changes in cellular metabolism also affect the function of effectors T cells through modifying epigenetic signatures. It is widely accepted that the dysfunction of T cell metabolism contributes greatly to T-cell exhaustion. Here, we reviewed recent findings on T cells metabolism under chronic viral infection, seeking to reveal the role of metabolic dysfunction played in T-cell exhaustion.